2006
DOI: 10.1111/j.1365-294x.2006.02814.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular ecology of zebra mussel invasions

Abstract: The invasion of the zebra mussel, Dreissena polymorpha, into North American waters has resulted in profound ecological disturbances and large monetary losses. This study examined the invasion history and patterns of genetic diversity among endemic and invading populations of zebra mussels using DNA sequences from the mitochondrial cytochrome oxidase I (COI) gene. Patterns of haplotype frequency indicate that all invasive populations of zebra mussels from North America and Europe originated from the Ponto-Caspi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
77
1
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(81 citation statements)
references
References 39 publications
1
77
1
2
Order By: Relevance
“…Human-introduced invasive species may serve as good surrogates for understanding processes of colonization and niche shifting (Levin, 2003), and we can probably gain a new perspective on these phenomena by viewing new species as successful invaders, and by using invasive species as a model system for understanding the early stages of speciation (Lee et al, 2003(Lee et al, , 2007. Both new species and introduced populations, for example, go through similar bottlenecks (May et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human-introduced invasive species may serve as good surrogates for understanding processes of colonization and niche shifting (Levin, 2003), and we can probably gain a new perspective on these phenomena by viewing new species as successful invaders, and by using invasive species as a model system for understanding the early stages of speciation (Lee et al, 2003(Lee et al, , 2007. Both new species and introduced populations, for example, go through similar bottlenecks (May et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, these invaders, freed of the natural controls of their native range, can proliferate in new waterways, displace native species and significantly degrade ecosystems. Well-known examples include the zebra mussel in North America (May et al, 2006), and the northern Pacific sea star in Tasmania (Ross et al, 2006). The latter was first collected in Tasmania in 1986, but its true identity was not realized until 1992, which shows the importance of taxonomic expertise in the study of invasive species.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have revealed the usefulness of genetic markers (e.g., RAPD, AFLP and microsatellites) as a tool to study the genetic structure of populations and infer source regions of invasion of Dreissena species (Wilson et al 1999;Stepien et al 2002;Pollux et al 2003;Elderkin et al 2004;Astanei et al 2005;Therriault et al 2005;May et al 2006). Phylogeographic analysis, expressing the hierarchical descent of populations, allows the identification of source regions by comparing the genetic similarity between the newly established population and potential surrounding source populations (Pollux et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…It has well-described negative impacts, such as obstructing pipelines (DSI, 2005) and fouling unionid mussels (Lewandowski, 1976;Schloesser et al, 1996). Although native to Turkey (e.g., May et al, 2006;Son, 2007), D. polymorpha also has negative effects in the Lake Sapanca basin. Most D. polymorpha collected 78 80 82 84 86 88 90 92 94 96 98 100 102 104 106 108 110 112 114 116 118 120 122 124 126 128 130 132 134 136 138 140 142 144 146 148 during the present study were only found attached to the shells of unionids.…”
Section: Discussionmentioning
confidence: 99%